World Economic Outlook January Update 2022. (World Economic Outlook; World Economic Outlook ;, 2022)
The global economy enters 2022 in a weaker position than previously expected. The COVID-19 Omicron variant has prompted new mobility restrictions, energy price increases and supply disruptions have spurred inflation more than anticipated, and the ongoing retrenchment of China's real estate sector and slower-than-expected private consumption have all been drags on global growth, The global economy enters 2022 in a weaker position than previously expected, with global growth forecast at 4.4 percent in 2022, half a percentage point slower than anticipated last October which is expected to moderate from 5.9 in 2021 to 4.4 percent in 2022-half a percentage point lower for 2022 than forecasted in October. The current forecast is predicated on improved vaccination rates and therapies worldwide by end-2022. The risks to this baseline forecast, however, tilt downward due to continued uncertainty in a number of areas, including the possibility of new COVID variants, prospects for a sudden tightening of financial conditions if inflation turns out higher than expected and monetary policy support in advanced economies is withdrawn faster than anticipated, geopolitical tensions, and the ongoing climate emergency.